Herpetofauna Community in The Karst Area of Pucung Village, Eromoko District, Wonogiri Regency - Muhammad Fakhri Aji Syahputra; Galuh Masyithoh; Ike Nurjuita Nayasilana (Jurnal Biodjati, 2025)
Pucung Village is located in Eromoko District, Wonogiri Regency, part of the Gunung Sewu karst area with diverse biodiversity, including herpetofauna (amphibians and reptiles). Limited information on the distribution patterns and abundance of herpetofauna is the focus of this study. This study examined herpetofauna diversity across three habitat types (river, forest, and field). Using Visual Encounter Surveys (VES) and line transects, 455 individuals from 19 species (10 families, 2 orders) were recorded. Forests exhibited the highest species diversity (H’ = 2.152 in Mijil, 1.873 in Dunggudel) and richness (R = 2.962 in Mijil, 2.392 in Dunggudel), attributed to structural complexity and niche availability. Fields showed high abundance but low diversity, dominated by Fejervarya cancrivora and Fejervarya limnocharis, indicating anthropogenic influence. River habitats displayed intermediate diversity, with variability linked to water quality and disturbance levels. Species similarity between habitats was moderate (53%), with the highest overlap between river and field habitats (72.73% in Mijil). Dispersed distribution patterns were observed, driven by water availability during the rainy season. Canonical Correspondence Analysis (CCA) revealed that water pH, temperature, and humidity significantly influenced herpetofauna presence, particularly for amphibians in field habitats. Future research should incorporate functional diversity metrics and long-term monitoring to assess climate and land-use effects.